Peran Kepemimpinan Transformasional Dalam Merespons Tantangan Modern di Lingkungan Birokrasi Publik Pemerintah Provinsi Sumatera Selatan - Suandi Suandi; Dwi Andriyani; Umi Purwanti; Rendy Sueztra Canaldhy (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research examines the role of transformational leadership in addressing modern challenges in the public bureaucracy of South Sumatra Province. Through a qualitative approach and single case study, field data successfully revealed the dynamics of leadership and the challenges faced in achieving transformational goals at the provincial level. Findings highlight the imbalance in focus on government vision and mission, lack of employee participation and engagement, challenges in technology implementation accompanied by human resource limitations, and policy instability due to the politicized local leadership selection system. Policy recommendations include aligning vision and mission to prioritize public service, efforts to increase employee participation, investment in technology-related human resource capacity development, and advocacy for reforming the local leadership selection system. Conclusion, these findings provide a comprehensive insight to guide improvements in leadership and policies in South Sumatra Province in addressing modern challenges in the public bureaucracy environment. Keywords: Modern Challenges, Public Bureaucracy Transformational Leadership,